Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

(g) x² (a+b) + 5x (a + b) +6 (a+b)


Sagot :

Solution:

      [tex]x^2(a+b)+5x(a+b)+6(a+b)\\\\=(a+b)(x^2+5x+6)\\\\=(a+b)\{x^2+(3+2)x+6\}\\\\=(a+b)\{x^2+3x+2x+6\}\\\\=(a+b)\{x(x+3)+2(x+3)\}\\\\=(a+b)(x+3)(x+2)[/tex]

                                                         

                                                         

x²(a+b) + 5x(a+b) +6(a+b)

= (a+b)(x²+ 5x +6)

=(a+b)(x²+3x+2x+6)

=(a+b){x(x+3)+2(x+3)}

=(a+b)(x+3)(x+2)